KESIAPAN PENERAPAN SAK EMKM DALAM PENYUSUNAN LAPORAN KEUANGAN PADA UMKM ZAMEL SNACK - Azmi, Alya Dian Nurul; Septiawati, Rohma; Nasihin, Ihsan (Institut Bisnis dan Teknologi Pelita Indonesia, 2025)
This study highlights the phenomenon of the limited understanding of the owner of Zamel Snack regarding the Financial Accounting Standards for Micro, Small, and Medium Entities (SAK EMKM). Currently, the business only records cash inflows and outflows, without preparing complete financial statements such as the balance sheet, income statement, statement of changes in equity, cash flow statement, and notes to the financial statements. This research aims to determine whether Zamel Snack has prepared financial statements in accordance with SAK EMKM and to assess the MSME's readiness in implementing the standard. The study employs a qualitative method using a descriptive approach through a case study at Zamel Snack. Data were collected through observation, interviews, and documentation, and were then analyzed using data triangulation techniques. The findings indicate that none of the six aspects recording system, business continuity, business entity concept, the owner's understanding of SAK EMKM, availability of human resources, and supporting information technology have been fully met. This research introduces a different approach by applying Grounded Theory to explore the readiness of Zamel Snack in implementing SAK EMKM, an approach that has not been widely used for this topic. This method allows the development of theory directly from field data, thereby providing new insights into the practical challenges faced by MSMEs in implementing SAK EMKM. Penelitian ini mengangkat fenomena keterbatasan pemahaman pemilik Zamel Snack terhadap Standar Akuntansi Keuangan Entitas Mikro, Kecil dan Menengah (SAK EMKM). Saat ini, mencatat kas masuk dan keluar, tanpa disertai laporan keuangan yang lengkap seperti neraca, laba rugi, perubahan modal, arus kas dan catatan atas laporan keuangan. Penelitian ini ditujukan untuk mengetahui UMKM Zamel Snack telah menyusun laporan keuangan sesuai SAK EMKM serta menilai kesiapan UMKM dalam menerapkannya. Penelitian ini menerapkan metode kualitatif melalui pendekatan deskriptif dengan studi kasus di UMKM Zamel Snack. Data diperoleh melalui observasi, wawancara, dan dokumentasi, kemudian dianalisis dengan menggunakan teknik triangulasi data. Temuan penelitian menghasilkan temuan bahwa dari enam aspek yaitu sistem pencatatan, kelangsungan usaha, konsep entitas bisnis, pemahaman pemilik usaha pada SAK EMKM, ketersediaan sumber daya manusia dan teknologi informasi pendukung belum ada yang sepenuhnya terpenuhi. Penelitian ini mengembangkan pendekatan berbeda melalui Grounded Theory untuk menggali kesiapan UMKM Zamel Snack dalam menerapkan SAK EMKM, yang belum banyak diterapkan pada topik ini. Pendekatan ini memungkinkan pembentukan teori yang bersumber langsung dari data lapangan, sehingga memberikan wawasan baru berkaitan dengan hambatan praktis yang dihadapi UMKM dalam pelaksanaan SAK EMKM.